2004
DOI: 10.1016/s0896-6273(03)00817-1
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Correlates of a Perceptual Decision in Ventral Premotor Cortex

Abstract: The ventral premotor cortex (VPC) is involved in the transformation of sensory information into action, although the exact neuronal operation is not known. We addressed this problem by recording from single neurons in VPC while trained monkeys report a decision based on the comparison of two mechanical vibrations applied sequentially to the fingertips. Here we report that the activity of VPC neurons reflects current and remembered sensory inputs, their comparison, and motor commands expressing the result; that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
324
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 305 publications
(358 citation statements)
references
References 33 publications
(7 reference statements)
23
324
1
1
Order By: Relevance
“…Accordingly, it remains to be determined whether motor learning leads to changes in somatosensory function in sensory or motor areas or the two in combination. Having somatosensory effects in motor areas of the brain would not be all that surprising, as there is ample evidence that cortical motor areas are extensively involved in somatosensory function (Romo et al 2004;Rosén and Asanuma 1972;Wong et al 1978).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, it remains to be determined whether motor learning leads to changes in somatosensory function in sensory or motor areas or the two in combination. Having somatosensory effects in motor areas of the brain would not be all that surprising, as there is ample evidence that cortical motor areas are extensively involved in somatosensory function (Romo et al 2004;Rosén and Asanuma 1972;Wong et al 1978).…”
Section: Discussionmentioning
confidence: 99%
“…We found that the activity of the recorded neurons of several cortical areas encodes f1 in a monotonic firing rate code beginning in the primary somatosensory cortex (5-7), continuing in the secondary somatosensory cortex (5), the ventral premotor cortex (19), the prefrontal cortex (10), and the medial premotor cortex (MPc) (18). Except for the primary somatosensory cortex, these cortical areas encode information of f1 during the delay period between f1 and f2 (5,10,11,(17)(18)(19). During presentation of f2, some neurons of all these cortical areas respond to f2, but some other neurons reflect past information of f1, or of the difference between f2 and f1, and generate a differential response consistent with the decision motor report (17)(18)(19).…”
mentioning
confidence: 99%
“…Except for the primary somatosensory cortex, these cortical areas encode information of f1 during the delay period between f1 and f2 (5,10,11,(17)(18)(19). During presentation of f2, some neurons of all these cortical areas respond to f2, but some other neurons reflect past information of f1, or of the difference between f2 and f1, and generate a differential response consistent with the decision motor report (17)(18)(19). In this chain of neural processes, the primary motor cortex becomes engaged only during the motor report period (19,21).…”
mentioning
confidence: 99%
“…TMS did not affect performance if delivered to the ipsilateral SI at any time point. The researchers proposed that the tactile memory trace was held initially for a certain period of time in both SI and SII, but later it would be held in higher level of cortex, such as the premotor and prefrontal cortex (Romo et al, 1999;Brody et al, 2003;Passingham and Sakai, 2004;Romo et al, 2004;Hernandez et al, 2002). A similar conclusion was drawn by a recent human fMRI study on haptic working memory (Kaas et al, 2007).…”
Section: Introductionmentioning
confidence: 86%